Reconstruction of Higher Education Curriculum Thinking Based on Philosophy and Theology According to Harun Nasution: Systematic Literature Review - Mad Sa'i; Muliatul Maghfiroh; Umi Sumbulah; Jamilah Jamilah; M. Yunus Abu Bakar; Zakki Fuad (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2026)
This study examines the reconstruction of philosophy- and theology-based curriculum thought developed by Harun Nasution as a framework for integrating Islamic sciences with general sciences in Islamic higher education. Using a Systematic Literature Review (SLR) approach, this research analyzes key scholarly works that discuss curriculum reform, the integration of knowledge, and the intellectual transformation of Islamic educational institutions influenced by Nasution’s rational-theological paradigm. The findings indicate that Nasution’s thought promotes an integrative model that harmonizes rationality and spirituality, thereby overcoming the traditional dichotomy between religious and general sciences. His framework emphasizes the incorporation of philosophy, theology, and modern social sciences as foundational pillars for expanding students’ intellectual capacity and fostering critical, analytical, and adaptive thinking. The study also confirms that this paradigm contributed significantly to the institutional transformation from IAIN to UIN and the strengthening of interdisciplinary academic traditions. The study concludes that Nasution’s approach provides a relevant and progressive basis for reconstructing the curriculum of Islamic higher education. Its practical implications include the adoption of discussion-based pedagogies, the enhancement of hermeneutic competence, and increased innovation in interdisciplinary research. Overall, this reconstruction offers a holistic and future-oriented model of Islamic higher education that responds effectively to contemporary global challenges, including those of the Industrial Revolution 5.0 era.